1984
DOI: 10.1115/1.3260881
|View full text |Cite
|
Sign up to set email alerts
|

Fretting: Load Carrying Capacity of Wear Debris

Abstract: Third body load carrying capacity noted with different materials under different kinematic conditions have been observed under fretting conditions. Tests run in the same machine with steel on steel, and chalk on glass, have shown similar particle shape and shape changes and similar particle motion. Observations show that third bodies formed with particles govern wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…As fretting is associated with very small displacement amplitudes, debris that is entrapped in the contact plays a critical role in the subsequent fretting wear behaviour; Iwabuchi [27] and Colombie & Berthier [28] argued that the role of debris within a fretting contact can either be protective, reducing wear, or act as an abrasive and increase wear. Protection by the retention of debris within the contact typically results from the debris preventing the first bodies (from which the debris is created) from interacting [29,30]; the severe adhesive wear associated with metalmetal contact is reduced, and the debris layer may also shear easily and thus accommodate the lateral motion.…”
Section: Discussion (A) Less-conforming Contactsmentioning
confidence: 99%
“…As fretting is associated with very small displacement amplitudes, debris that is entrapped in the contact plays a critical role in the subsequent fretting wear behaviour; Iwabuchi [27] and Colombie & Berthier [28] argued that the role of debris within a fretting contact can either be protective, reducing wear, or act as an abrasive and increase wear. Protection by the retention of debris within the contact typically results from the debris preventing the first bodies (from which the debris is created) from interacting [29,30]; the severe adhesive wear associated with metalmetal contact is reduced, and the debris layer may also shear easily and thus accommodate the lateral motion.…”
Section: Discussion (A) Less-conforming Contactsmentioning
confidence: 99%
“…Previous studies [10][11][12][13] indicate that the presence of the oxide debris in the fretting contact can significantly influence the wear behaviour, with Godet [10] proposing the concept of the debris acting as the third body between the wearing surfaces which prevents direct contact between the primary surfaces. Iwabuchi et al [14] studied the role of the debris by artificially supplying oxide particles into the contact (as opposed to the oxides being formed by the wear process itself) and concluded that the formation of a stable and compacted oxide layer will result in a reduction in wear, but if such a layer does not develop, the wear rate will be increased by the oxide particles acting as an abrasive.…”
Section: Introductionmentioning
confidence: 99%
“…Iwabuchi et al [14] studied the role of the debris by artificially supplying oxide particles into the contact (as opposed to the oxides being formed by the wear process itself) and concluded that the formation of a stable and compacted oxide layer will result in a reduction in wear, but if such a layer does not develop, the wear rate will be increased by the oxide particles acting as an abrasive. In further experiments to understand the role of the oxide in fretting, Colombie et al [12] performed tests which were periodically interrupted to allow removal of the debris from the contact; these tests provided further evidence regarding the significance of the debris bed in determining fretting behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…But, this is far from truth in dry friction, especially for ceramic materials 27,28 . Fretting experiments have clearly shown that wear debris decreases the wear of materials 27 .…”
Section: Discussionmentioning
confidence: 99%
“…But, this is far from truth in dry friction, especially for ceramic materials 27,28 . Fretting experiments have clearly shown that wear debris decreases the wear of materials 27 . Compared with ceramic materials, wear debris is looser and can also respond kinematically to the velocity mismatch, and accordingly, causes less damage than that occasioned by locked asperities of the mated material with identical hardness 28 .…”
Section: Discussionmentioning
confidence: 99%